The Yelwata Maroua 1er festival in Cameroon: a semio-hermeneutic approach to a popular culture - Boho, Zacharie Hatolong (Íkala, Revista de Lenguaje y Cultura, 2016)
Yelwata Maroua 1er is an annual festival organized by the mayor of Maroua I in Cameroun and held in a multidimensional stadium named Complexe Sportif Maroua Domayo. The object of this paper is the study of language practices –language and pictorial signs– that are generally produced on the stadium wall. These messages with a double semiotic status are analyzed to study diversity,local and national celebrities, collective memory and Cameroonian people expectations. The methodological framework consists of direct observation, photography and semio-hermeneutic analysis. The theoretical context is based on the ethno-morphological model usually applied to plastic art.